Hyperfine fields of sp impurities on Ni and Fe surfaces - P. Mavropoulos; N. Stefanou; B. Nonas; R. Zeller; P.H. Dederichs (PHYSICAL REVIEW LETTERS, 1998)
We present first-principles calculations of the electronic structure and hyperfine fields of 4sp impurities un the (001) surfaces of Ni and Fe. The calculations are based on the local-spin-density functional theory and employ a Green's function method for impurities at surfaces. The systematic behavior obtained for the hyperfine fields of adatoms or impurities in the first surface layer is completely different from that found in the bulk, mainly due to the reduction of the symmetry and the coordination number at the surface. Our results explain the surprisingly small hyperfine-field values measured for Se adatoms and provide challenging predictions to be confirmed by future experiments.